Non-performing loans: what matters in addition to the economic cycle? - Roland Beck; Petr Jakubik; Anamaria Piloiu (European Central Bank (ECB), 2013)
Using a novel panel data set we study the macroeconomic determinants of nonperforming loans (NPLs) across 75 countries during the past decade. According to our dynamic panel estimates, the following variables are found to significantly affect NPL ratios: real GDP growth, share prices, the exchange rate, and the lending interest rate. In the case of exchange rates, the direction of the effect depends on the extent of foreign exchange lending to unhedged borrowers which is particularly high in countries with pegged or managed exchange rates. In the case of share prices, the impact is found to be larger in countries which have a large stock market relative to GDP. These results are robust to alternative econometric specifications.
Keywords: G21; G28; G32; F34; 330; Credit risk; currency mismatches; non-performing loans